Abundance of Silkworms (Tubifex sp) Fed Swallow Faeces as an Alternative Natural Feed for Ornamental Fishes - Akebai, Janawi; Achmad, Khamsiah; Murhum, Mufti Abdul.; Yuliana, Yuliana; Mutmainnah, Mutmainnah; Dody, Safar (University of Pattimura, 2024)
The ornamental fish in the aquaculture business is growing over time and continuing to be a promised sector. To ensure success, the presence of natural feed is crucial for the larvae stage. Tubifex has a high protein content and can provide all the nutrition fish larvae need. This study aims to rear tubifex in mud media and fed by swallow feces in four doses: 50 grams, 100 grams, and 150 grams, respectively, and without feces as a control. Results show that giving 150 grams of swallow feces increases the growth and abundance of tubifex in about 1174.33 individuals in 30 days. Water quality parameters such as temperature, pH, dissolved oxygen (DO), and ammonia support the survival of tubifex.